2014
DOI: 10.2478/hukin-2014-0112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climbing Ability and Slope Inclination on Vertical Foot Loading Using a Novel Force Sensor Instrumentation System

Abstract: The aim of the study was to assess the effects of climbing ability and slope inclination on vertical loading both in terms the forces involved and physiological responses. Five novice and six intermediate female climbers completed a climbing route at three slope inclinations (85°, 90°, and 98°). The vertical loading during the climb was assessed by force-time integral using a Novel Pedar-X insole and physiological responses via oxygen uptake and heart rate. The novice climbers had a significantly lower (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
(17 reference statements)
2
23
0
Order By: Relevance
“…Consequently, these dimensions maximise potential finger flexor activation. The testing position saw the arm placed at 180° shoulder flexion and full elbow extension according recommendations made by Baláš et al (2014). All measurements were undertaken in seated position with the shoulder of the tested arm placed vertically under the wooden hold ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, these dimensions maximise potential finger flexor activation. The testing position saw the arm placed at 180° shoulder flexion and full elbow extension according recommendations made by Baláš et al (2014). All measurements were undertaken in seated position with the shoulder of the tested arm placed vertically under the wooden hold ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Rock-climbing requires equilibrating and moving the entire body along routes across walls, boulders, and cliffs, using quadrupedal locomotion. It requires many physical (Baláš, 2017), psychological (Sanchez, 2017), technical (Baláš et al, 2014;Quaine, Martin, Leroux, Blanchi, & Allard, 1996), and cognitive skills (Bourdin, Teasdale, & Nougier, 1998;Epling, Blakely, Russel, & Helton, 2017). These include the crucial capacities to exert strong fingertip forces on the holds and pull ups with the upper limbs to reach the next hold (Draper, Dickson, Blackwell, Priestley, Fryer, Marshall, Shearman, Hamlin, Winter & Ellis, 2011;Watts, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As this ability group has the lowest experience with the sport, climbing to height might have presented a more mentally demanding condition resulting in changes in the use of forces on hold during ascent. Previously, it has been demonstrated that less experienced climbers disproportionally load their arms than their legs, thereby increasing their physiological response when compared with higher-grade climbers (Baláš et al, 2014). In agreement with this difference, RPE has been found to be higher during arm exercise than with leg exercise (G. Pandolf et al, 1984;Borg et al, 1987).…”
Section: Discussionmentioning
confidence: 72%